Conventional and complementary alternative medicine therapies for renal anemia: a literature review - Lu, Ching-Ming; Hsu, Yuan-Hsuan; Lin, I-Hsin; Kuo, Ko-Lin; Liao, Jian-Fu; Huang, Hui-Fen; Lu, Ping-Hsun (Frontiers in Endocrinology, 2025)
Renal anemia stems mainly from chronic inflammation with elevated hepcidin levels, iron deficiency, and reduced red blood cell lifespan. Inadequate erythropoietin (EPO) production, worsened kidney function, leads to symptoms such as low energy, fatigue, and impaired physical function, significantly affecting patients’ quality of life. We conducted a comprehensive search across electronic databases including PubMed, Embase, Cochrane Library, Chinese National Knowledge Infrastructure, Airiti library, and Wanfang, to compile recent clinical trials and pilot studies on conventional and complementary alternative medicine approaches for renal anemia. This discussion focuses on the hypoxia-inducible factor prolyl hydroxylase domain (HIF-PHD) axis theory, from lab research to clinical applications. It explores non-extracorporeal treatments for renal anemia, including pharmaceutical interventions, dietary strategies, and complementary and alternative medicine (CAM). The article details the effects of Roxadustat, Ferumoxytol, and Epodion.Clinical studies show that modulating the gut microbiome can reduce inflammation and improve renal anemia. Clinical trials suggest that CAM therapy can improve renal anemia through mechanisms such as enhanced iron metabolism, anti-inflammatory effects, reduced hepcidin levels, and increased EPO and HIF expressions. By synthesizing this information, the review aims to furnish valuable insights and treatment recommendations aimed at ameliorating renal anemia in individuals grappling with chronic kidney disease.